Conversation Analysis and Politeness Theory are used to investigate the lack of communication in Tennessee Williams' The Glass Menagerie - Assist. Lect. Alaa Raheem Farhan (Peerian Journals Publishing, 2024)
The goal of this study is to perform a study on Communication Breakdown in Tennessee William’s famous play ‘‘The Glass Menagerge’’ with reference to Conversation Analysis and Politeness theory. The main purpose is to explore what is hidden behind failures in language interactions of various characters in the play. This research proposal will aim at analyzing the communication breakdown and its consequences in Tennessee Williams’ play The Glass Menagerie. From our results, it can be seen that there are some crucial patterns that help explain many other features of dialogue and interactions. First of all, there is an evident tendency to avoid dialogues, hesitate, and convey information indirectly, which resulted in the actual impossibility of interaction. The causes of a lack of directness include great social pressure, personal insecurity, and psychological barriers. Furthermore, the interpretation of the play brings a view of power conflict within the process of the communication into perspective. Power relationships between characters such as dominance and submission result in silence allowing some characters limited voice. Such a scenario only amplifies existing misconceptions and eliminates the chance of reconciliation that could be started by different parties involved in the conflict. Also, Politeness Theory shows how different tactics are used by characters in the attempt to avoid FTA so that the social relationships among them are not damaged; however, such efforts negatively interfere with actual communication creating confusion and interpersonal conflict among people. The findings of the study reveal that there are real-life communication issues in literary texts and effective communication strategies include the use of open-ended questions and the practice of effective communication in interpersonal relationships. As such, the study seeks to contribute to the understanding of communication breakdowns in literary texts by employing conversation analysis and politeness theory.
Keywords: Face work; FTA; dramatic speech